2004
DOI: 10.1890/04-0341
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of an Invasive Plant: An Experimental Study With Silene Latifolia

Abstract: The damage caused by biological invasions has traditionally been thought to result from alien species taking advantage of ecological differences between the native and introduced ranges. In contrast, the role of evolutionary forces has received relatively little attention. Our results show that evolutionary change in Silene latifolia, a North American weed that was introduced from Europe about 200 years ago, can help explain the plant's successful North American invasion. By growing plants from seed collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
218
6
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(247 citation statements)
references
References 47 publications
(46 reference statements)
21
218
6
1
Order By: Relevance
“…Interestingly, most of the evidence for phenotypic clines with climate was in Europe, with very few variables approaching significance in North America. Previous studies in S. latifolia have reported divergence in life history traits among European populations (Delph et al, 2002;Wolfe et al, 2004), and one trait (age at first flowering) has previously been shown to exhibit clinal variation with latitude ( Jolivet & Bernasconi, 2007). There is also phenotypic divergence between Europe and North America consistent with adaptive evolution, although not expressly clinal in nature (Blair & Wolfe, 2004;Wolfe et al, 2004).…”
Section: Species Differences In Clinal Differentiationmentioning
confidence: 83%
“…Interestingly, most of the evidence for phenotypic clines with climate was in Europe, with very few variables approaching significance in North America. Previous studies in S. latifolia have reported divergence in life history traits among European populations (Delph et al, 2002;Wolfe et al, 2004), and one trait (age at first flowering) has previously been shown to exhibit clinal variation with latitude ( Jolivet & Bernasconi, 2007). There is also phenotypic divergence between Europe and North America consistent with adaptive evolution, although not expressly clinal in nature (Blair & Wolfe, 2004;Wolfe et al, 2004).…”
Section: Species Differences In Clinal Differentiationmentioning
confidence: 83%
“…One explanation is that natural selection in the absence of enemies shifts the optimal investment of resources from defence to enhanced growth and reproduction. S. latifolia was introduced to North America approximately 200 years ago, and there are large differences in the species' biology between the two continents: (1) S. latifolia has escaped some specialist enemies during colonization, and damage levels are higher in Europe (Wolfe, 2002); (2) North American plants are 'weedier' and more reproductively prolific (Blair and Wolfe, 2004), and they invest less in defence and have lower resistance to fungal infection and fruit predation . The development of genomic tools for Silene will soon allow dissection of the genetic changes associated with successful invasions.…”
Section: Biological Invasionsmentioning
confidence: 99%
“…Yet, many introduced species have expanding range margins and thus can provide insights into important evolutionary processes that drive adaptation and range expansion (9,10). Over a relatively short time interval, some invasive plants have evolved higher growth and reduced anti-herbivore defenses (11,12), higher sexual and/or clonal reproductive rates (13,14), and have adapted to local climatic conditions (15,16). Thus far, the influence of species immigration history on such high adaptive potential of newly founded populations has been little investigated.…”
mentioning
confidence: 99%